Divergence correction for three-dimensional magnetotelluric forward modelling with arbitrary electrical anisotropy - Guo Yu; Jing Han (Frontiers in Earth Science)
This paper presents an enhanced framework for three-dimensional (3D) magnetotelluric (MT) forward modeling that incorporates a current density divergence correction procedure for arbitrary anisotropic conditions. The method accelerates the convergence of iterative solvers in solving forward equations in anisotropic media. The divergence correction is adapted from techniques initially developed for isotropic MT modeling. Through four numerical examples—a 1D anisotropic model, a 2D anisotropic model with an infinite lateral fault overlying perfect conductor, a 2D anisotropic model with upper and lower structure and a challenging 3D anisotropic model with random parameters—the validity and efficiency of the proposed approach are demonstrated. The results show that the incorporation of divergence correction significantly reduces the number of iterations required for convergence, improving computational performance and stability. The framework proves robust even in demanding scenarios involving long periods and complex anisotropic structures.